Provenance and Sediment Maturity as Controls on CO2 Mineral Sequestration Potential of the Gassum Formation in the Skagerrak - Olivarius, Mette; Sundal, Anja; Weibel, Rikke; Gregersen, Ulrik; Baig, Irfan; Thomsen, Tonny B.; Kristensen, Lars; Hellevang, Helge; Nielsen, Lars Henrik (Frontiers in Earth Science, 2019)
In order to meet the increasing demand to decarbonize the atmosphere, storage of CO2 in subsurface geological reservoirs is an effective measure. To maximize storage capacity, various types of saline aquifers should be considered including dynamic storage options with open or semi-open boundaries. In sloping aquifers, assessment of the immobilization potential for CO2 through dissolution and mineralization along the flow path is a crucial part of risk evaluations. The Gassum Formation in the Skagerrak is considered a nearshore CO2 storage option with sloping layers, facilitating buoyant migration of CO2 northwards along depositional and structural dip. In this study, petrographic data and provenance analysis provide the basis for estimating reactivity of the sandstones. Immobilization of CO2 in the reservoir through fluid dissolution and mineral reactions reduces risk of leakage. Petrographic analyses are integrated with seismic and well-log interpretation to identify sedimentary facies and to estimate mineral distribution with corresponding reactivity in the proposed injection area. Here the Gassum Formation comprises south-prograding, shoreface-fluvial para-sequences, sourced from northern hinterlands. Pronounced differences in the mineralogical maturity in the studied area are identified and explained by the sediment transport distances and the type of sediment source. This is possible because the U-Pb ages of zircon grains in the sediments can be used to pinpoint the areas where they originate from in the Fennoscandian Shield, such as the Telemarkia or Idefjorden terranes. Albite and Fe-rich chlorite are identified as the most reactive mineral phases in the Gassum sand, of which feldspar comprises the largest weight fraction and the grain-coating chlorite has largest surface area. Their distribution is partly controlled by provenance, so their abundance decreases basinwards with increasing sediment maturity. The abundance of fluvial sandstones presumably increases northwards in basal parts of para-sequences, while shoreface sandstones comprise the top part of sandy units. CO2 injected in the proposed area will migrate upwards within the reservoir, toward higher proportions of Telemarkian-derived sediment and up-dip along the seal, toward more immature sediments. Thus, the reactivity of sediments increases in younger deposits and up depositional dip, while kinetic reaction rates will decrease in shallower, lower temperature regions. Identifying these parameters is important to estimate the CO2 mineral sequestration potential as a function of sedimentary facies and ensure safe storage of CO2. This approach can advantageously be applied to all reservoirs considered for CO2 injection to improve the estimation of the possible CO2 storage volume by taking the provenance dependence of the mineralization potential into account.